Role and Mechanism of the Renin-Angiotensin-Aldosterone System in the Onset and Development of Cardiorenal Syndrome - Ma, Kexin; Gao, Weifang; Xu, Huazhou; Liang, Wenjie; Ma, Guoping (Journal of the Renin-Angiotensin-Aldosterone System, 2022)
Cardiorenal syndrome (CRS), a clinical syndrome involving multiple pathological mechanisms, exhibits high morbidity and mortality. According to the primary activity of the disease, CRS can be divided into cardiorenal syndrome (type I and type II), renal heart syndrome (type III and type IV), and secondary heart and kidney disease (type V). The renin-angiotensin-aldosterone system (RAAS) is an important humoral regulatory system of the body that exists widely in various tissues and organs. As a compensatory mechanism, the RAAS is typically activated to participate in the regulation of target organ function. RAAS activation plays a key role in the pathogenesis of CRS. The RAAS induces the onset and development of CRS by mediating oxidative stress, uremic toxin overload, and asymmetric dimethylarginine production. Research on the mechanism of RAAS-induced CRS can provide multiple intervention methods that are of great significance for reducing end-stage organ damage and further improving the quality of life of patients with CRS.